Almetrics: A bibliometric review from 2015 to 2020 - Avendaño Espinoza, Betzabeth Yajaira (Advanced Notes in Information Science, 2022)
A bibliometric analysis is carried out around the scientific production on Altmetrics between the years 2015-2020 in the Scopus database. For this, the present study consists of two parts, in the first, a review of the literature on Altmetrics is made, where the main characteristics are pointed out. In the second part, the results of the bibliometric analysis are presented, in which a total of 714 publications are analyzed based on indicators such as the number of publications per year and journals, topics, affiliations, and collaboration between researchers and countries. To obtain other indicators for the analysis of the journals, the Scimago Journal Rank (SJR) was consulted, where indicators such as the impact factor and the quartile that each journal belongs to were obtained. The scientific production on Altmetrics has a significant growth each year and this growing trend tends to increase. There is a variety of disciplines in journals that publish around Altmetrics, not remaining exclusively in the library or information science journals.